2015
DOI: 10.1371/journal.pbio.1002328
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Network Organization and Integration to the Development of Cognitive Control

Abstract: Cognitive control, which continues to mature throughout adolescence, is supported by the ability for well-defined organized brain networks to flexibly integrate information. However, the development of intrinsic brain network organization and its relationship to observed improvements in cognitive control are not well understood. In the present study, we used resting state functional magnetic resonance imaging (RS-fMRI), graph theory, the antisaccade task, and rigorous head motion control to characterize and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
267
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 282 publications
(315 citation statements)
references
References 87 publications
(148 reference statements)
35
267
5
1
Order By: Relevance
“…The authors contend that their results are consistent with notions that network development facilitates the ability to traverse through more diverse cognitive states in order to accomplish increasingly complex task demands (Bassett et al, 2011; Braun et al, 2015). Similar, albeit not identical developmental findings, are observed by (Marek et al, 2015)), who found increased cross-network integration between the cingulo-opercular/salience and somatomotor modules over the age of 10–26, which they showed to be associated with the development of cognitive control. In agreement with these data, two additional reports also had findings that suggested that functional restructuring over this timespan disproportionately involves the cingulo-opercular and somotomotor modules (Fair et al, 2012b; Grayson et al, 2014), and potentially specific links between them (Grayson et al, 2014) (see Figure 4).…”
Section: Developmental Refinements Of Network Structure Into Adulthoodsupporting
confidence: 83%
See 3 more Smart Citations
“…The authors contend that their results are consistent with notions that network development facilitates the ability to traverse through more diverse cognitive states in order to accomplish increasingly complex task demands (Bassett et al, 2011; Braun et al, 2015). Similar, albeit not identical developmental findings, are observed by (Marek et al, 2015)), who found increased cross-network integration between the cingulo-opercular/salience and somatomotor modules over the age of 10–26, which they showed to be associated with the development of cognitive control. In agreement with these data, two additional reports also had findings that suggested that functional restructuring over this timespan disproportionately involves the cingulo-opercular and somotomotor modules (Fair et al, 2012b; Grayson et al, 2014), and potentially specific links between them (Grayson et al, 2014) (see Figure 4).…”
Section: Developmental Refinements Of Network Structure Into Adulthoodsupporting
confidence: 83%
“…It is likely, however, that functional network maturation follows more precise spatiotemporal trajectories than previously understood. Indeed, there are now at least 3 reports that suggest the network structure in children as defined by community detection (see Figure 3) are largely similar to the adult (Fair et al, 2012b; Marek et al, 2015; Power et al, 2012). Despite this “adult like” level of organization, refinements within and between systems does appear to occur over time, although details to this end are still being worked out (Fair et al, 2012b; Gu et al, 2015b; Marek et al, 2015).…”
Section: Developmental Refinements Of Network Structure Into Adulthoodmentioning
confidence: 99%
See 2 more Smart Citations
“…Like recent publications (65;66), we used a rigorous rsfMRI processing pipeline to account for head motion and used several processing pipeline (Supplemental Materials). …”
Section: Methodsmentioning
confidence: 99%